Male-male Aggression in Rhinoceros unicornis - Case Study from North Bengal, India - Yadav, V. K. (Indian Forester, 2000)
The present study analyses the aggressive behaviour of male Rhinos. Dominant adult male Rhinoceros attack frequently weak aged male Rhino and subadult Rhinos, who are recently weaned from mother. They try to establish supremacy by show of strength with other male Rhinos for mating with females in oestrus. Injuries inflicted during repeated intra-species fighting are many times fatal and lead to the death of weak males. The present study indicates that the dominant male Rhino frequently encroach upon the home range of other weak male Rhinos and compel them to leave the areas and restrict their movement to a particular area due to frequent attacks.